2009
DOI: 10.3758/pbr.16.5.778
|View full text |Cite
|
Sign up to set email alerts
|

Why does picture-plane inversion sometimes dissociate perception of features and spacing in faces, and sometimes not? Toward a new theory of holistic processing

Abstract: 778Face recognition is critical for our daily social interactions. The ease with which we discriminate among the thousands of faces that we encounter throughout our life is remarkable, given the very similar structure and features that all faces share. An important contribution to this ability, which is found for upright but not inverted faces, is presumed to be a style of perceptual processing commonly referred to as holistic (Tanaka & Farah, 1993), configural ), or second-order relational (Diamond & Carey, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
249
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(271 citation statements)
references
References 66 publications
(159 reference statements)
19
249
2
1
Order By: Relevance
“…Importantly, the main effect of Face Orientation is largely consistent with the qualitative account of face inversion effect (Le Grand et al, 2001;McKone & Yovel, 2009;Rhodes et al, 1993;Rossion, 2009;Rossion & Boremanse, 2008), suggesting that upright faces are processed as such irrespective of the background scene orientation. However, when we took correct reaction time into account, the IE data suggested that congruency with the scene had a different impact on upright faces than it did on inverted faces; congruency facilitated performance when faces were upside down.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Importantly, the main effect of Face Orientation is largely consistent with the qualitative account of face inversion effect (Le Grand et al, 2001;McKone & Yovel, 2009;Rhodes et al, 1993;Rossion, 2009;Rossion & Boremanse, 2008), suggesting that upright faces are processed as such irrespective of the background scene orientation. However, when we took correct reaction time into account, the IE data suggested that congruency with the scene had a different impact on upright faces than it did on inverted faces; congruency facilitated performance when faces were upside down.…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, by using a number of different photographs to represent each identity, we have eliminated any concern that participants were able to determine matching pairs based on image properties, rather than faces per se. Therefore, this method of using multiple photographs of highly familiar faces may prove useful in the future because it avoids both the problems normally associated with simultaneous matching tasks and those associated traditional recognition memory paradigms (for recent reviews, see McKone & Yovel, 2009;Rossion, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Answers to these questions will not only help reconcile the discrepancies between mixed findings about holistic processing of moving faces, but they will also help address one fundamental question about current theories of holistic processing-whether they can be generalized to moving stimuli or apply only to static faces and objects. Moreover, determining whether holistic and part-based processing are similarly involved between static and rigidly moving faces may also help clarify what is holistic representation of faces (McKone & Yovel, 2009;Piepers & Robbins, 2012;Rossion, 2013) and what type of facial information underlies holistic processing (Rossion, 2013;Zhao et al, 2016b). …”
Section: The Present Studymentioning
confidence: 99%